2021
DOI: 10.1186/s12889-021-10172-6
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating participation in cardiovascular preventive initiatives among people with diabetes: a qualitative study

Abstract: Background Type 2 diabetes (T2D) is associated with a significantly increased risk of cardiovascular disease (CVD). The DIAbetic CArdioVAscular Screening and intervention trial (DIACAVAS) was designed to clarify whether advanced imaging for subclinical atherosclerosis combined with medical treatment is an effective strategy to develop individualised treatment algorithms for Danish men and women with T2D aged 40–60. But in the DIACAVAS pilot study, the uptake was only 41%. Consequently, we explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…The authors elaborate that diabetic patient categized by powerlessness often feel overwhelmed living with the chronical illness. This can lead to predominance of their emotions and a limited ability to undertake diabetes self-care tasks (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors elaborate that diabetic patient categized by powerlessness often feel overwhelmed living with the chronical illness. This can lead to predominance of their emotions and a limited ability to undertake diabetes self-care tasks (31).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the patient capacity, experience, and role in in the healthcare can be useful in working towards an increased health literacy for the patient. In addition, it is also suggested that health literacy may facilitate a proactive and health-promoting in diabetic self-care (31).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to cope with diabetes has also been discussed in a study by Dahl et al The authors reported that diabetic patients who feel powerless are often overwhelmed by chronic illness. This can lead to a limited ability to undertake diabetes self-care tasks [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding patients’ capacity, experience, and role in healthcare can be useful for improving health literacy. In addition, health literacy may facilitate proactive and health-promoting diabetes self-care [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation